Cost-Effectiveness and Budget Impact of Emicizumab Prophylaxis in Haemophilia A Patients with Inhibitors - Cortesi, Paolo Angelo; Castaman, Giancarlo; Trifirò, Gianluca; Creazzola, Simona Serao; Improta, Giovanni; Mazzaglia, Giampiero; Molinari, Angelo Claudio; Mantovani, Lorenzo Giovanni (Thrombosis and Haemostasis, 2020)
Recent evidence demonstrated that weekly prophylaxis with subcutaneous bispecific antibody (emicizumab) has shown higher efficacy in adolescent and adults patients affected by haemophilia A (HA) with inhibitor, compared with patients treated on demand or on prophylaxis with bypassing agents (BPAs). However, no economic evaluations assessing the value and sustainability of emicizumab prophylaxis have been performed in Europe. This study assessed the cost-effectiveness of emicizumab prophylaxis compared with BPA prophylaxis and its possible budget impact from the Italian National Health Service (NHS) perspective. A Markov model and a budget impact model were developed to estimate the cost-effectiveness and budget impact of emicizumab prophylaxis in HA patients with inhibitors. The model was populated using treatment efficacy from clinical trials and key clinical, cost and epidemiological data retrieved through an extensive literature review. Compared with BPAs prophylaxis, emicizumab prophylaxis was found to be more effective (0.94 quality adjusted life-years) and cost saving (–€19.4/–€24.4 million per patient lifetime) in a cohort of 4-year-old patients with HA and inhibitors who failed immune tolerance induction. In the probabilistic sensitivity analysis, emicizumab prophylaxis had always 100% probability of being cost-effective at any threshold. Further, the use of emicizumab prophylaxis was associated to an overall budget reduction of €45.4 million in the next 3 years. In conclusion, the clinically effective emicizumab prophylaxis can be considered a cost-saving treatment for HA with inhibitor patients. Furthermore, emicizumab treatment is also associated to a significant reduction of the health care budget, making this new treatment a sustainable and convenient health care option for Italian NHS.
Keywords: haemophilia A; inhibitors; prophylaxis; cost-effectiveness; budget impact